The Implementation of Bilingual Class Program in Islamic Elementary School - Amalia, Ila; Marzuki, Abdul Gafur (AT-TA'LIM, 2023)
For several decades, the expanding usage of English as an international language has resulted in a growth in its users all over the world, including in Indonesia. As a result, the bilingual education program becomes a medium for promoting English in society. This case study investigated the implementation of a bilingual class program at an Islamic elementary school in Indonesia, namely in Banten province. The participants of the study included a bilingual teacher, the school principal, the vice-principal for student affairs, and the vice-principal for curriculum division. Interviews, classroom observations, and documentation were utilized to collect the data. Meanwhile, the Miles and Huberman data analysis technique was employed to analyze the data, which consisted of data reduction, data display, and conclusion. The results elaborated on some aspects related to the practice of bilingual class programs in this school namely: the aspect of school administration, the aspect of human resources, the aspect of teaching and learning activities, and the aspect of program evaluation. The findings also revealed that the school adopted partial immersion as the bilingual program model.